Design of a smart device to maintain relief over the carpal tunnel syndrome symptoms - Gutiérrez-Brenes, Tamara (2025)
Carpal Tunnel Syndrome CTS is one of the most common work-related conditions in recent years, associated with repetitive movements and efforts on the wrist. Symptoms such as pain, numbness, tingling and loss of strength in the hand and wrist cause the person to have difficulty using their hand, limiting their daily activities and unable to perform their work. The syndrome was an implicit sentence of the reduction in quality of life of the person who suffers it, and for this very reason ALIVCA was born. Through a research and design process in 5 stages, the idea was conceptualized, shaped, gave functionalities, tested, designed and finished. At the end of this trip, it was established what is ALIVCA, an intelligent wearable device for the forearm composed of a control panel where therapies and notifications are managed, and the zone called "H" which can provide transcutaneous electrostimulation therapy at 6 different points and heat transfer therapy. The impact of the product was found in improving quality of life for people with CTS, this was achieved by being able to provide this population with the ability to relieve their pain in an effective way, easily accessible and without having to stop their daily activity by the impediment that symbolizes pain.